Mixed viral infection constrains the genome formula of multipartite cucumber mosaic virus - Boezen, Dieke; Vermeulen, Maritta; Johnson, Marcelle L.; van der Vlugt, René A. A.; Malmstrom, Carolyn M.; Zwart, Mark P. (Frontiers in Virology, 2023)
Many plant viruses have a multipartite organization, with multiple genome segments packaged into separate virus particles. The genome formula describes the relative frequencies of all viral genome segments, and previous work suggests rapid changes in these frequencies facilitate virus adaptation. Many studies have reported mixed viral infections in plants, often resulting in strong virus–virus interactions. Here, we tested whether mixed infections with tripartite alfalfa mosaic virus (AMV) and monopartite potato virus Y (PVY) affected the genome formula of the tripartite cucumber mosaic virus (CMV), our experimental model. We found that the CMV titer was reduced in mixed infections with its tripartite Bromoviridae relative AMV and in triple infections with both AMV and PVY, indicating notable virus–virus interactions. The variability of the CMV genome formula was significantly lower in mixed infections (CMV and AMV, CMV and PVY, and CMV and AMV and PVY) than in single infections (CMV only). These observations led to the surprising conclusion that mixed infections with two distinct viruses constrain the CMV genome formula. It remains unclear how common these effects are for different combinations of virus species and strains and what the underlying mechanisms are. We, therefore, extended a simulation model to consider three putative scenarios in which a second virus affected the genome formula. The simulation results also suggested that shifts in the genome formula occur, but may not be widespread due to the required conditions. One scenario modeled—co-infection exclusion through niche differentiation—was congruent with the experimental data, as this scenario led to reductions in genome formula variability and titer of the multipartite virus. Whereas previous studies highlighted host–species effects, our results indicate that the genome formula is also affected by mixed infections, suggesting that there is a broader set of environmental cues that affect the genome formula.